2019
DOI: 10.1111/trf.15351
|View full text |Cite
|
Sign up to set email alerts
|

A national Transfusion Register of Irregular Antibodies and Cross (X)‐match Problems: TRIX, a 10‐year analysis

Abstract: BACKGROUND: The Transfusion Register of IrregularAntibodies and Cross-match Problems (TRIX) is a unique national database in the Netherlands that was launched in 2007. Transfusion laboratories register the presence of irregular RBC alloantibodies for their patients and can consult the database for information that is relevant for pretransfusion testing, unknown in their own laboratory information system. STUDY DESIGN AND METHODS:Data from the TRIX database 10 years after implementation have been analyzed to de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
27
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(30 citation statements)
references
References 26 publications
1
27
0
Order By: Relevance
“…Transfusion medicine registries have prevented DHTRs caused by antibody evanescence and transfusion medicine record fragmentation. The work of van Gammern and coworkers has demonstrated the technical feasibility of a registry on a national scale . These authors also demonstrated an important step in the future development of registries, namely, engagement with BBIS vendors.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Transfusion medicine registries have prevented DHTRs caused by antibody evanescence and transfusion medicine record fragmentation. The work of van Gammern and coworkers has demonstrated the technical feasibility of a registry on a national scale . These authors also demonstrated an important step in the future development of registries, namely, engagement with BBIS vendors.…”
Section: Discussionmentioning
confidence: 99%
“…This investigation along with similar, smaller‐scale studies can help us to determine the number of DHTRs potentially preventable with a transfusion medicine registry. Van Gammeren and coworkers reported 1014 antibody disappearance registrations, defined as an antibody tested for, but undetectable due to evanescence . This number is likely an underestimate given that 50% of sites did not report antibody disappearance registrations.…”
Section: The Safety Benefits Of a Transfusion Medicine Registrymentioning
confidence: 99%
See 2 more Smart Citations
“…Because antibodies may lose detectability over time, accurate recording and accessibility of patient antibody formation is of the utmost importance [93,95,102]. Besides in-hospital records, a national database is available in the Netherlands (TRIX, Transfusion Register Irregular antibodies and X(cross)-matching), in which hospitals register patients with RBC antibodies and cross-match problems [120]. This system is accessed for the evanesced antibodies in all patients with a transfusion request to prevent re-exposure to the cognate antigen.…”
Section: Current Matching Strategies In the Netherlandsmentioning
confidence: 99%